The experimental method of middle distance runners hypoxic training - Kuznetsova, Z.; Morozov, A.; Kuznetsov, A. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
The study is focused on the problem of various hypoxic effects use in the training process of athletes specializing in middle distance running. The purpose - to develop and experimentally justify the method of interval hypoxic training in the annual cycle of middle distance runners training. Hypothesis: the development and application of interval hypoxic training method, which provides the consistent use of hypoxia, adequate structure and volume of different directions training loads in weekly microcycles, will improve the training efficiency and middle distance runners competitive activity effectiveness.The method of hypoxic training includes hypoxic and information tools:Hypoxicator "Peak"(Russia) realizes exogenous type of hypoxia and consists of series connected: mask, the body (filled with absorber of carbon dioxide) and a breathing bag. Diaphragm mask "Elevation training mask"(USA) implements respiratory type of hypoxia. To estimate athletes heart rate monitoring we used the me thod of obtaining information wireless portable system GPS Garmin Forerunner 310XT (Garmin, USA).The concentration of oxygen in the blood was investigated using pulse oximeter "Oxy-Pulse"(Russia). Hypoxic training technique of athletes specializing in middle distance running is scientifically proved, developed and experimentally checked.